PERAN TATA KELOLA PERBANKAN SYARIAH TERHADAP RISIKO PERBANKAN SYARIAH DI INDONESIA - Rudy Hartanto (Universitas Pamulang, 2020)
The increased penetration of the Islamic banking market in Indonesia is one of the highest in ASIA. The enhancement in the market has an impact on increasing the risk complexity of Islamic banking business activities. Sharia banking risks need to be managed and controlled properly in order to prevent banking failures. Bank governance (corporate governance) is indicated as one of the things that plays an important role in determining the level of risk faced by banks. The purpose of this study is to examine whether good governance can reduce the risk of Islamic banking. This study uses the population of Islamic banking from 2014-2018. The samples obtained in this study are 58 Islamic banks. The results showed that good governance can reduce the banking risk. In addition, the testing using control variables showed that the greater the size of the banking system that is proxied by the total assets, the higher the risk received by banks both from credit risk to investment risk.